Mitigating emotional responses to stressors: coping strategies, modifiers and support. (April 2022) - Dennis, D.; van Heerden, P.V; Knott, C.; Khanna, R.
Objective: The stressful nature of the intensive care unit (ICU) environment is increasingly well characterised. The aim of this paper was to explore modifiers, coping strategies and support pathways identified by experienced Intensivists, in response to these stressors. Method: Prospective qualitative study employing interviews with Intensivists in two countries. Participants were asked how they mitigated their emotional responses to the stressors of the ICU. Audio-recordings were transcribed and analysed by all researchers who agreed upon emerging themes and subthemes. Results: A wide range of strategies were reported. Although several participants had sought professional help and all supported its utility, few disclosed accessing such help to others indicating stigma. Many felt a sense of responsibility for the well-being of other staff but identified barriers that suggest alternate support pathways are required. Further implications of these findings to training considerations are described. Conclusions: Several approaches were described as regularly employed by Intensivists to mitigate ICU environmental stressors. Intensivists perceive themselves to have limited training to provide support to others; they also perceive stigma in seeking professional help.